Strategies to avoid humidity causing damages in tall timber buildings - Silva, Catarina V. (2016)
The number of tall housing buildings using cross laminated timber (CLT) as the main structural material has been growing all around the world but especially in Europe. This kind of construction has already proven to be a solution with a sustainable profile and despite the conflicts with some building codes and some countries legislation, this construction material is able to shape safe structures. However, to get the full confidence of the public, several researches focused on main CLT restrictions are still under development, such as fire safety, strength of connections, structural behavior, acoustics and durability. This last point is of huge importance considering timber’s propensity for rotting and its known hygroscopic behavior. If humidity effects are not considered during the building design as well as the structure’s integrity the people’s wellbeing can be compromised. The content of the present paper aims to outline important recommendations concerning the reduction of humidity causing damages in tall timber buildings. For that, CLT/glulam hybrid construction system (Urban Timber system) is used to illustrate and describe suggested construction details of a timber building, from the foundations to the roof: the most cautious solution for foundations is to resort to reinforced concrete, in case of biological attacks or unexpected hazards; facades have to ensure the protection of timber structural elements from contact with moisture either through insulation materials or by glazed walls; windows in contact with timber ends should be able to prevent water to reach them; connection between timber elements must predict swelling/shrinkage movements of timber; at least an efficient rain water drainage has to be guaranteed by the balconies and the roof design.